2015
DOI: 10.9771/cmbio.v13i3.12933
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da Doença de Parkinson na funcionalidade e qualidade de vida de idosos em uma unidade de referência geriátrica na cidade de Salvador - Bahia

Abstract: <p class="MsoNormal" style="text-align: justify;"><strong><span style="font-size: 11.0pt;">Introdução: </span></strong><span style="font-size: 11.0pt;">Doença de Parkinson (DP) é a segunda enfermidade neurodegenerativa mais prevalente entre idosos. Os indivíduos acometidos por essa doença podem experimentar prejuízos funcionais, emocionais e sociais durante a progressão da doença, com impacto negativo na qualidade de vida (QV). <strong>Objetivo: </strong>Descreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
2
4
0
1
Order By: Relevance
“…This finding corroborates the results reported in the literature, in which mild PD is characterized by complete functionality and moderate PD by functional impairment due to the more severe signs and symptoms, which act as precursors of disability 13,14 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding corroborates the results reported in the literature, in which mild PD is characterized by complete functionality and moderate PD by functional impairment due to the more severe signs and symptoms, which act as precursors of disability 13,14 .…”
Section: Discussionsupporting
confidence: 82%
“…Here, these symptoms were more important in individuals in the MOG, who had a mean disease duration of eight years, compared with three years in the MIG 17,20 . The greatest impairment in terms of quality of life in the MOG was observed in the domains of mobility, stigma, cognition and ADLs, corroborating the findings of studies by Navarro-Peternella et al, 9 Pinheiro et al, 13 Navarro-Peternella and Marcon 14 , and Quintella et al 21 In the mobility domain, having difficulty doing pleasurable leisure activities was one factor that adversely affected quality of life, a finding also reported in studies by Mandira 22 and Tavares et al 23 . Normal mobility is required to perform ADLs and leisure activities; reduced mobility compromises performance of these activities, limits the activities that can be performed and increases the time required to perform them.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The present study found a worse perception of QoL in the domains of body discomfort, social support, and mobility, demonstrating that PD shows a multidimensional character [ 26 ]. In addition, the mean total score of the PDQ-39 was above 50 (53.2 ± 15.2), demonstrating a perception of low QoL by the interviewed patients.…”
Section: Discussionmentioning
confidence: 81%
“…Com o aumento da expectativa de vida, estima-se que por volta de 2020 a doença acometa mais de 40 milhões de pessoas no mundo (FREITAS et al, 2006;LIMA et al, 2010;QUINTELLA et al, 2013;PINHEIRO, I. et al, 2014). A DP acomete o sistema nigroestriataldopaminér-gico e clinicamente é caracterizada por distúrbios do movimento, da postura e do equilíbrio, manifestando-se por meio de acinesia, rigidez, tremor de repouso e instabilidade postural (FREITAS et al, 2006;SANT et al, 2008;LIMA et al, 2010).…”
Section: Introductionunclassified